Strong time-periodic solutions to the bidomain equations with arbitrary large forces. (June 2019) - Giga, Yoshikazu; Kajiwara, Naoto; Kress, Klaus
Abstract: We prove the existence of strong time-periodic solutions to the bidomain equations with arbitrary large forces. We construct weak time-periodic solutions by a Galerkin method combined with Brouwer's fixed point theorem and a priori estimate independent of approximation. We then show their regularity so that our solution is a strong time-periodic solution in L 2 spaces. Our strategy is based on the weak–strong uniqueness method.